Boosting Hemoglobin: The Power of Dates and Honey for Third Trimester Pregnant Women - Nurseha, Nurseha; Utami Subagio, Sri; Arifiati, Nurce; Suwardiman, Deni (Journal of Pharmaceutical and Health Research, 2024)
Anemia poses a significant health challenge, particularly among pregnant women, with Indonesia facing a notable burden in maternal mortality rates (MMR). This study investigates the efficacy of date fruit and honey supplementation in addressing anemia among third-trimester pregnant women attending Kramatwatu Community Health Center. Drawing on a quantitative approach with a quasi-experimental design, the research aims to elucidate the impact of this intervention on hemoglobin (HB) levels. The prevalence of anemia among pregnant women is alarming, with all respondents in the study experiencing anemia before the intervention. However, following the provision of date fruit and honey, a substantial increase in HB levels was observed, indicating a promising avenue for improving maternal health outcomes. Utilizing SPSS for analysis, univariate and bivariate analyses were conducted to describe variables and test intervention effects. The study underscores the potential effectiveness of date fruit and honey supplementation in ameliorating anemia among pregnant women, although further research is warranted to ascertain long-term efficacy and optimal dosages. Comprehensive interventions addressing nutritional deficiencies and healthcare access are crucial for advancing maternal health goals and reducing MMR in Indonesia.